Martí Caloca, Ivette. «Todo se ha hecho a mi voluntad»: Melibea como eje central de «La Celestina». Madrid: Iberoamericana, 2019 (Medievalia Hispánica, vol. 26). 208 pp. ISBN 978-84-9192-062-5 - Snow, Joseph T. (Celestinesca, 2021)
N/A